First de novo transcriptome analysis of the Antarctic springtail Cryptopygus terranovus (Collembola: Isotomidae) following mid-term heat exposure. Issue 5 (October 2021) - Cucini, Claudio; Leo, Chiara; Nardi, Francesco; Greco, Samuele; Manfrin, Chiara; Giulianini, Piero G.; Carapelli, Antonio
Abstract: Global human activities, such as greenhouse emissions and pollution, are promoting global warming, environmental changes and biodiversity reduction. Pristine environments such as those of Antarctica are not immune to these phenomena, as is noticeable from the increasing pace of the temperature shift registered within the continent in recent decades. In this study, we describe the first de novo transcriptome analysis of the endemic Antarctic springtail (= collembolan) Cryptopygus terranovus and we evaluate its global gene expression response following a mid-term exposure of 20 days to 18°C. Expression data are compared with wild specimens sampled from their native environment to outline the molecular mechanisms triggered by the thermal exposure. Although individual plasticity in transcript modulation is assessed, several pathways appear to be differentially modulated in springtails subjected to the heat treatment vs wild specimens. Through enrichment analysis, we show that protein catabolism, fatty acid metabolism and a sexual response characterized by spermatid development are induced, while carbohydrate consumption, lipid catabolism and tissue development are downregulated in treated samples compared to controls.